Response of serum biochemical profile, antioxidant enzymes, and gut microbiota to dietary Hong-bailanshen supplementation in horses - Ding, Jinxue; Gu, Bolin; Meng, Jinwu; Hu, Mengxin; Wang, Wenjia; Liu, Jiaguo (Frontiers in Microbiology, 2024)
Background Traditional Chinese medicine (TCM) is widely used in humans and animals, which is very important for health. TCM affects the body ‘s immunity and changes in intestinal flora. This study was conducted to investigate the effects of dietary Hong-bailanshen (HBLS) supplementation in horses on serum biochemical profile, antioxidant enzymes and gut microbiota. Methods In this study, five horses were selected. On day 0, 14, 28, blood samples and feces were collected on days 0, 14, and 28 to analyse gut microbiota, serum biochemical and redox indexes. Results The results showed that the addition of HBLS to horse diets significantly decreased the level of alanine aminotransferase, alkaline phosphatase, creatine kinase and malondialdehyde (p < 0.05, p < 0.01) and significantly increased the activity of total antioxidant capacity, superoxide dismutase and catalase (p < 0.05, p < 0.01). Compared with day 14, the levels of alanine aminotransferase, alkaline phosphatase and creatine kinase were significantly decreased; however, the level of catalase was significantly increased in the horses continuously fed with HBLS for 28 days (p < 0.05, p < 0.01). Alpha diversity analysis was performed that chao1 (p < 0.05), observed_specicies, faith’pd and goods_coverage upregulated in the horses fed HBLS. A total of 24 differential genera were detected adding HBLS to diet increased the abundance of Bacillus, Lactobacillaceae, Leuconostocaceae, Christensenellaceae, Peptostreptococcaceae, Faecalibacterium, Erysipelotrichaceae, Pyramidobacter, Sphaerochaeta, WCHB1-25, Bacteria, Oscillospira, and Acetobacteraceae, while reduced Aerococcus, EtOH8, Syntrophomonas, Caulobacter, Bradyrhizobiaceae, W22, Succinivibrionaceae, and Desulfovibrio (p < 0.05, p < 0.01). Conclusion Adding HBLS to the diet could be a potentially effective strategy to improve horses’ health.